2011
DOI: 10.1111/j.1468-1331.2010.03158.x
|View full text |Cite
|
Sign up to set email alerts
|

H63D polymorphism in the hemochromatosis gene is associated with sporadic amyotrophic lateral sclerosis in China

Abstract: The HFE H63D polymorphism may contribute to the development of sALS in Chinese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…There is increasing evidence suggesting an association between H63D HFE and ALS [18][19][20][21][22]. Even studies in which a significant increase in H63D HFE was not found in ALS patients compared to the controls [23][24][25] the percentage of ALS patients with H63D HFE is consistently reported at around 30%.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There is increasing evidence suggesting an association between H63D HFE and ALS [18][19][20][21][22]. Even studies in which a significant increase in H63D HFE was not found in ALS patients compared to the controls [23][24][25] the percentage of ALS patients with H63D HFE is consistently reported at around 30%.…”
Section: Discussionmentioning
confidence: 89%
“…However, increasing evidence suggests an association of H63D HFE with neurodegenerative diseases including ALS [17]. Five independent groups in the United States [18], the United Kingdom [19], Italy [20], the Netherlands [21] and China [22] have reported a positive association between H63D HFE and ALS. Although three studies [23][24][25] reported no association between H63D HFE and ALS, in all studies, there is agreement that H63D HFE is present in as many as 30% of ALS patients [18][19][20][21][23][24][25].…”
Section: Introductionmentioning
confidence: 97%
“…The model is consistent with the human population studies where H63D is a genetic modifier for ALS. The frequency of this polymorphism is as high as 30 % in sporadic ALS patients compared to 14 % in the control populations (Connor and Lee 2006;Goodall et al 2005;He et al 2011;Restagno et al 2007;Sutedja et al 2007;Wang et al 2004). The C282Y polymorphism has been linked to PD (Dekker et al 2003;Guerreiro et al 2006) and multiple sclerosis (Ristic et al 2005).…”
Section: Er Stress and Neurodegenerative Diseasementioning
confidence: 92%
“…The first report examining the presence of HFE mutations in ALS found no association between two mutations (H63D and C282Y) and ALS patients from the USA (Yen et al, 2004). However, several subsequent studies in a total of 1133 ALS patients and almost 7000 controls individuals from the USA, Ireland, UK, Italy, The Netherlands, and China reported association between the HFE H63D polymorphism and an increased risk for ALS (Goodall et al, 2005;He et al, 2011;Restagno et al, 2007;Sutedja et al, 2007;Wang et al, 2004).…”
Section: Haemochromatosis (Hfe)mentioning
confidence: 99%